O uso do scratch como ferramenta de contextualização matemática - SANTOS, Lucas Carvalho dos (2023)
This research entitled The use of scratch as a mathematical contextualization tool was developed with the aim of helping to correct a deficiency that is evident in education: the lack of resources and adapted materials to contextualize the teaching of mathematics in underserved communities. Observing the significant growth of TDICs (Digital Information and Communication Technologies) in recent years, a proposal was sought to create an electronic game using the Scratch platform, to be an alternative and attractive tool for students from these communities who are inserted in a regrettable statistic: the high truancy. The game entitled Mathematical Adventure narrates the daily life of a riverside character who shows how mathematics is found in everyday life, in addition to working on some of the skills and competencies of the BNCC (Common National Curriculum Base), stimulating mathematical thinking and interest in programming languages . In this way, the idea proposes to benefit from the aptitude of the current generation in the use of information technologies to add to the solution of the presented problem.